TUNGKU TIGO SAJARANGAN PADA ERA GLOBALISASI DAN VISUALISASI DALAM KRIYA SENI - Niko Andeska; Dharsono Sony Kartika; Martion Martion (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT This article is the research result about the existence of Tungku Tigo Sajarangan role and then it is visualized through craftwork. Minangkabau is one of the ethnicities or cultures that has uniqueness namely its system of leadership that consists of ninik mamak (customary leaders), alim ulama (religious leaders), and cerdik pandai (intelligent people). These three elements are called as Tungku Tigo Sajarangan. Tungku Tigo Sajarangan is the interconnected leadership that has the important role in the wheel of customary, religious, and knowledgeable leadership. The fast current development and the big external influence result on the appearance of societal diseases. Hence, it results on the author’s wariness toward the existence of Minangkabau philosophy “adat basandi syarak, syarak basandi kitabullah.” Tungku Tigo Sajarangan as the source of the idea for the craft creation is quite representative because the leadership of Tungku Tigo Sajarangan has an adequate phenomenon to be used as an aspiration in the creation of craftwork, and also as the answer for the worry of the loss of Tungku Tigo Sajarangan leadership’s role. Keywords: Tungku Tigo Sajarangan, Globalization, Craft